Respuesta :
(-4, 6)
The center-radius form of a circle is the equation
(x - h)^2 + (y - k)^2 = r^2
where
(h,k) = center of circle
r = radius of circle.
Since the equation that was given is (x + 4)^2 + (y - 6)^2 = 25. then
(x - h) = (x + 4)
-h = 4
h = -4
(y - k) = (y - 6)
- k = - 6
k = 6
So the center is (h,k) = (-4,6)
Answer:
(-4, 6)
Step-by-step explanation:The center-radius form of a circle is the equation (x - h)^2 + (y - k)^2 = r^2 where (h,k) = center of circle r = radius of circle. Since the equation that was given is (x + 4)^2 + (y - 6)^2 = 25. then (x - h) = (x + 4) -h = 4 h = -4 (y - k) = (y - 6) - k = - 6 k = 6 So the center is (h,k) = (-4,6)